P Peran tri pusat pendidikan terhadap keterampilan sosial anak berkebutuhan khusus di SD Muhammadiyah Nitikan Yogyakarta - Muhammad Rizqi Maylamirsyah; Banun Havifah Cahyo Khosiyono (Universitas Sarjanawiyata Tamansiswa, 2023)
The purpose of this study is to understand the role of the Three Education Centers on the social skills of children with special needs at SD Muhammadiyah Nitikan. The subjects in this study were school principals, grade III teachers, grade III teachers, special assistant teachers, parents of a student with special needs, committees, peers, and students with special needs at SD Muhammadiyah Nitikan. Data collection techniques used observation techniques, interviews, and documentation. The data analysis technique in this study used Miles and Huberman which consists of data collection, data reduction, data presentation, and conclusion. The results showed that (1) the family environment plays a role in the first and foremost educators of children, guarantees children's comfort and happiness, and the occurrence of constant social interactions, motivates children. (2) The school environment plays a role in children's formal education that is directed and structured, providing facilities to support children's needs, as well as giving encouragement and support to children. (3) The community environment becomes a place for children's social activities, as well as supporting children's social skills. (4) Obstacles to the implementation of the three education centers are found in the children with special needs themselves, the lack of responsiveness of the family environment to reports from schools, the school environment that could not accompany children 100%, and the community environment who is less aware of the importance of social skills of children with special needs. (5) The efforts of the three education centers towards the development of social skills are the provision of adequate facilities, open-mindedness, and good communication between the three environments, organizing meetings to conduct cooperation in shaping children's social skills, giving examples, and instilling social skills during the learning process.